Authenticities philosophical reflections on musical performance - Kivy, Peter 1934-2017 (Cornell Univ. Press, 1995)
How are we to assess the current popularity of period instruments and early-music performance? For musicians and audiences alike, the "historical authenticity" movement has increasingly influenced the performance of classical music. It has given us, claims Peter Kivy, "new and rewarding ways of listening to our musical repertory (as well as silly, vulgar, and unrewarding ones)." He believes that theory now overrules the ear in arguing for and justifying particular aesthetic decisions. In his customary engaging style, Kivy here mounts a philosophical inquiry into the desirability of using or re-creating historical practices in performance. In "How to Be Authentic," the first section of his book, he examines four different kinds of authenticity; in the second part, "Why to Be Authentic," he suggests how to evaluate them. Discussing issues that he cares about passionately, Kivy provides ammunition for both camps - those who follow authentic performance practice and those who do not